Light and Shade in Marine Conservation Across European and Contiguous Seas - Fraschetti, Simonetta; Pipitone, Carlo; Mazaris, Antonios D.; Rilov, Gil; Badalamenti, Fabio; Bevilacqua, Stanislao; Claudet, Joachim; Carić, Hrvoje; Dahl, Karsten; D’Anna, Giovanni; Daunys, Darius; Frost, Matthew; et al. (Frontiers in Marine Science, 2018)
As a response to increasing human pressures on marine ecosystems, the legislation aimed at improving the conservation and management of marine coastal areas in European and Contiguous Seas (ECS) underwent crucial advances. ECS, however, still remain largely affected by increasing threats leading to biodiversity loss. Here, by using emblematic case studies and expert knowledge, we review current conservation tools, comparing their application in different areas to assess their effectiveness, potential for synergies, and contradictions. Despite regional differences in their application, the existing legislative frameworks have the potential to regulate human activities and to protect marine biodiversity. However, four challenges remain to be addressed to fully achieve environmental policy goals: 1) Lack of shared vision representing a limitation in transboundary collaboration. Although all EU countries are committed to fulfil EU Directives and other binding international legislative acts, a remarkable heterogeneity exists among countries in the compliance with the common legislation on conservation and in their degree of implementation. 2) Lack of systematic procedures for the selection of protected marine sites. Regional and national approaches in designating Natura 2000 sites and nationally designated Marine Protected Areas (MPAs) reflect varying conservation targets and importance of conservation issues in political agendas. 3) Lack of coherent ecological networks. Natura 2000 sites and other MPAs are still far from reaching the status of effective networks in all considered case studies. 4) Hotspot of conflicts with private economic interests prevailing over conservation aims. Recommendations are given to overcome the fragmented approach still characterizing the conservation and management of coastal marine environments. Holistic, integrated, ecosystem-based, cross-cutting approaches can avoid conflicts among institutions so as to provide effective and timely solutions to current and future challenges concerning the conservation and management of marine ecosystems and associated goods and services.